The United Nations and Contemporary International Peace and Security: Challenges, Effectiveness and Reform in the Twenty-First Century - Dr. Prem Singh (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The United Nations (UN) has remained the principal international organization entrusted with the responsibility of maintaining international peace and security since its establishment in 1945. Created in the aftermath of the Second World War, the organization has played a significant role in conflict prevention, peacekeeping, peacebuilding, humanitarian assistance, and the promotion of international cooperation. However, the changing nature of global politics, increasing geopolitical rivalries, and the emergence of non-traditional security threats have raised important questions regarding the effectiveness of the United Nations in fulfilling its mandate. This study critically examines the role of the United Nations in maintaining international peace and security in the twenty-first century. It analyses the contributions of the organization through its peacekeeping operations, collective security mechanisms, conflict resolution efforts, and humanitarian interventions while also examining the institutional, political, and operational challenges that constrain its effectiveness. The study adopts a qualitative research methodology based on secondary data collected from books, peer-reviewed journal articles, official United Nations reports, and policy documents. Drawing upon the theoretical perspectives of Liberal Institutionalism and Realism, the paper argues that although the United Nations continues to serve as the cornerstone of global governance and multilateral diplomacy, its effectiveness is increasingly influenced by the competing strategic interests of major powers, particularly within the Security Council. The paper concludes that meaningful institutional reforms, including the restructuring of the Security Council, improved peacekeeping mechanisms, enhanced financial sustainability, and greater international cooperation, are necessary to strengthen the United Nations' ability to address contemporary security challenges. Despite its limitations, the United Nations remains indispensable for promoting international peace, stability, and collective security in an increasingly complex global order.